About Utilization Efficiency Evaluation of Gas-Expansion and Generator Units at Thermal Power Stations - S. A. Kachan; A. A. Bazylenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers methods for determination of gas-expansion and generator unit indices when they are applied at a thermal power station. It is shown, that while relating the effect of additional power-and-heat generation output due to heat taking-off from steam turbines to gas-expansion and generator unit to the operation of this unit a specific fuel consumption of power supply from gas-expansion and generator unit can be lower than fuel equivalent of kilowatt-hour.